2016
DOI: 10.5897/ajar2016.11211
|View full text |Cite
|
Sign up to set email alerts
|

Morphological diversity and identification of accessions of melon

Abstract: Family agriculture is a rich germplasm source wherever it takes place; however, information on genetic variability of this type of culture in Brazil is scarce. Samples of melon (Cucumis melo L.) accessions grown by family agriculture were rescued and this study aimed at characterizing the genetic variability in one sample of these accessions so as to identify the melon subspecies and the corresponding varieties. Fifteen accessions and their S 1 progenies were characterized (quantitative and qualitative descrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(19 citation statements)
references
References 16 publications
2
17
0
Order By: Relevance
“…The data of analysis of variance showed significant differences among melon sub-accessions for all characteristics evaluated (Table 2), denoting the existence of genetic variability among sub-accessions. Similar results were found in previous studies on melon accessions from traditional agriculture (AMORIM et al, 2016;MACÊDO et al, 2017;ANDRADE et al, 2019), supporting those found in the present study and, therefore, denoting the possibility of selecting agronomically superior accessions for the characteristics analyzed (CRUZ; REGAZI; CARNEIRO, 2012). Means followed by same lowercase letter in the columns, or uppercase letter in the rows, are not statistically different from each other by the Scott Knott test at 5% significance.…”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…The data of analysis of variance showed significant differences among melon sub-accessions for all characteristics evaluated (Table 2), denoting the existence of genetic variability among sub-accessions. Similar results were found in previous studies on melon accessions from traditional agriculture (AMORIM et al, 2016;MACÊDO et al, 2017;ANDRADE et al, 2019), supporting those found in the present study and, therefore, denoting the possibility of selecting agronomically superior accessions for the characteristics analyzed (CRUZ; REGAZI; CARNEIRO, 2012). Means followed by same lowercase letter in the columns, or uppercase letter in the rows, are not statistically different from each other by the Scott Knott test at 5% significance.…”
Section: Resultssupporting
confidence: 93%
“…Prolificacy and fruit cavity diameter presented only 18.5% variation, highlighting the variety makuwa and botanical varieties not defined (ND), respectively. Regarding the other characteristics, the highest variations were found for sub-accessions of ND varieties (Table 2); these variations are probably because of the high variability among plants within the sub-accessions, which is due to the introgression of alleles among different botanical varieties (MACÊDO et al, 2017;AMORIM et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations